Cognitive bias and how to improve sustainable decision making - Korteling, Johan. E. (Hans); Paradies, Geerte L.; Sassen-van Meer, Josephine P. (Frontiers in Psychology, 2023)
The rapid advances of science and technology have provided a large part of the world with all conceivable needs and comfort. However, this welfare comes with serious threats to the planet and many of its inhabitants. An enormous amount of scientific evidence points at global warming, mass destruction of bio-diversity, scarce resources, health risks, and pollution all over the world. These facts are generally acknowledged nowadays, not only by scientists, but also by the majority of politicians and citizens. Nevertheless, this understanding has caused insufficient changes in our decision making and behavior to preserve our natural resources and to prevent upcoming (natural) disasters. In the present study, we try to explain how systematic tendencies or distortions in human judgement and decision making, known as “cognitive biases”, contribute to this situation. We first briefly present the social-psychological characteristics (or dimensions) that are inherent to (or typical for) most sustainability issues. These are: experiential vagueness, long-term effects, complexity and uncertainty, threat of the status quo, threat of social status, social dilemma’s, and group pressure. For each of these characteristics we describe how this relates to cognitive biases, from a neuro-evolutionary point of view, and how these evolved biases may affect sustainable choices or behaviors of people. Finally, we suggest influence techniques (nudges, incentives) to mitigate or capitalize on these biases in order to foster more sustainable choices and behaviors